266 Intra-epithelial spreading of cervical squamous cell carcinoma to the upper genital tract. (13th November 2020) - Shi, X; Wu, S; Liu, Y; Cui, Q; Liang, Z
Abstract : This study was designed to describe the clinicopathological characteristics of cervical squamous cell carcinoma (SCC) intra epithelial spreading to the upper genital tract. A total of fifteen patients were enrolled, including eleven patients which were cervical SCC spreading to the endometrium, four patients whose squamous cell carcinoma intra epithelial spread along the uterine cavity to the adnexa. Clinical information and pathological data were collected. Human high risk HPV was detected by mRNA in situ hybridization. The average age was 55.07 years old. Twelve of the fifteen patients were post menopause women. The intra epithelial spread pattern can be seen in thirteen patients. Five of the fourteen patients received a uterine apoxesis, the other pre operative condition including chemotherapy, papillary thyroid carcinoma, thyroid hypofunction, and immune deficiency. HPV was positive in all the patients' specimen, and the infection status of cervical lesions, endometrial lesions, and adnexal lesions were same. For the peculiar case twelve, the cervical CIS lesion intra epithelial spread along the mucosa of uterine cavity and fallopian tube, and invasive SCC can be identified in the uterine corpus, fallopian tubes and ovaries. Intra epithelial spread pattern is an indolent spreading pathway of the cervical SCC, it can involve the upper uterine tract even when the cervical lesion in at a very early stage, such as CIS. The deepest invasion site may not be the primary site. The intra epithelial spread may have relationship with pre operative disposal. High risk HPV detection can help to confirm the cervical origination.